San Marino : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper reviews economic developments in San Marino during 1990-98. San Marino has enjoyed rapid growth in the 1990s, as the expansion in output has outstripped that experienced in Italy as a whole and the surrounding regions of Emilia-Romagna and the Marche. Real GDP rose by an average of about 10 percent per year in 1992-94 and an estimated 5 percent in 1996 and 1997. Employment rose sharply in the early 1990s before slowing down to an average of 3 percent in 1996-97.